THE IMPORTANCE OF THE INTEGRATION PROCESS IN TEACHING ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The integration process in teaching English is one of the important principles that help make the learning process of the language more effective and meaningful for students. Integration, by combining different disciplines and skills, gives students the opportunity to learn more broadly and in-depth. This process aims to increase students ' learning motivation, develop their thinking skills, and expand English, interactive programs, integration, culture, art, communication, problems.their opportunities for practical language use.